Rancang Bangun Spin Coater Vakum Chuck Berbasis Mikrokontroler dengan Tuning PID Metode Ziegler-Nichols - Bayu Septiawan; Laili Mardiana; Lalu Sahrul Hudha (Indonesian Journal of Applied Science and Technology, 2025)
Spin coating is a thin-film deposition method that utilizes centrifugal force to produce uniform coatings; however, commercial instruments are expensive and therefore difficult to access for educational laboratories. This study aims to design and develop an ESP32-based spin coater equipped with a vacuum chuck system and motor speed control using a PID algorithm, with parameter tuning based on the Ziegler–Nichols method. The research methodology includes hardware and software design, component selection such as a brushed DC motor XD-3420, KY-003 Hall effect sensor, BTS7960 motor driver, and a vacuum system to hold the substrate. Performance testing was conducted through RPM sensor calibration, determination of optimal PWM frequency, and comparison between conventional control and PID control. The results show that the developed system is capable of reaching a maximum speed of 8500 rpm with a resolution of 0.1 rpm, linearity of 99.94%, and accuracy of 98.72% compared to a tachometer. The optimal operating frequency range of the system is 6000–8000 Hz with a sensitivity of 366.08 rpm/volt. PID control provides the best performance with a response time of 300 ms, an overshoot of 21.14%, and a steady-state error of 42.8 rpm. In conclusion, the proposed spin coater delivers precise and stable speed control, making it suitable for thin-film–based materials research in educational laboratories.